Proteomic analysis of lipopolysaccharide activated human monocytes. (November 2018) - Lausen, Mads; Poulsen, Thomas B.G.; Christiansen, Gunna; Kastaniegaard, Kenneth; Stensballe, Allan; Birkelund, Svend
Highlights: LC–MS/MS analysis identifies 2746 quantifiable proteins in human monocytes. LPS alters the abundance of 244 proteins. LPS reduces the abundance of several lysosomal proteins. LPS alters the abundance of proteins involved in antigen-presentation and skews antigen-presentation towards MHC class I presentation. Abstract: Monocytes are key mediators of innate immunity and comprise an important cellular defence against invading pathogens. However, exaggerated or dysregulated monocyte activation can lead to severe immune-mediated pathology such as sepsis or chronic inflammatory diseases. Thus, detailed insight into the molecular mechanisms of monocyte activation is essential to understand monocyte-driven inflammatory pathologies. We therefore investigated the global protein changes in human monocytes during lipopolysaccharide (LPS) activation to mimic bacterial activation. Purified human monocytes were stimulated with LPS for 17 h and analyzed by state-of-the-art liquid chromatography tandem mass spectrometry (LC–MS/MS). The label-free quantitative proteome analysis identified 2746 quantifiable proteins of which 101 had a statistically significantly different abundance between LPS-stimulated cells and unstimulated controls. Additionally, 143 proteins were exclusively identified in either LPS stimulated cells or unstimulated controls. Functional annotation clustering demonstrated that LPS, most significantly, regulates proteasomal- and lysosomal proteins but in opposite directions. Thus, seven proteasome subunits were upregulated by LPS while 11 lysosomal proteins were downregulated. Both systems are critically involved in processing of proteins for antigen-presentation and together with LPS-induced regulation of CD74 and tapasin, our data suggest that LPS can skew monocytic antigen-presentation towards MHC class I rather than MHC class II. In summary, this study provides a sensitive high throughput protein analysis of LPS-induced monocyte activation and identifies several LPS-regulated proteins not previously described in the literature which can be used as a source for future studies.